Rheumotologitsts’ view on the use of hydroxychloroquine to treat COVID-19 - Xiaoxuan Sun; Yicheng Ni; Miaojia Zhang (Emerging Microbes and Infections)
The current pandemic coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) calls urgently for effective therapies. Anti-malarial medicine chloroquine (CQ) and particularly its chemical analogue hydroxychloroquine (HCQ) have been recommended as promising candidate therapeutics that are now under either compassionate off-label use or clinical trials for the treatment of COVID-19 patients. However, there are public concerns and disputes about both the safety and efficacy of CQ and HCQ for this new application. Given the fact that for decades HCQ has been approved as an immunomodulatory drug for the long term treatment of chronic rheumatic diseases, as experienced rheumatologists, we would like to share our thoughts in this regard and trigger a brainstorm among clinical care providers for exchanging their diverse opinions on this urgent topic.